Circumstances to Be Clarified under the Investigation of Interference into Law Enforcement Officer’s Activity (Law and Safety, 2021)
The author has substantiated the need to establish the circumstances to be clarified and has determined their significance during the investigation. It has been emphasized that the circumstances to be clarified include the circumstances to be proved in criminal proceedings, criminal and forensic characteristics of a criminal offense.In order to determine the circumstances to be clarified during the investigation of interference in the activities of a law enforcement officer, the author has studied the circumstances to be clarified within the group of criminal offenses related to obstruction of the activities of a law enforcement officer, as well as during the investigation of interference in the activities of a forensic expert. Taking into account the specified scientific provisions, the author has defined a detailed list of circumstances to be clarified during the investigation of interference in the activities of a law enforcement officer.It has been established that the circumstances to be clarified during the interference in the activities of a law enforcement officer include:1) circumstances related to the criminal offense, namely: time, place, situation and traces of a criminal offense, methods of its commission (preparation, direct commission and concealment), tools and means used during the interference, the scope of procedural costs; circumstances that are the basis for ceasing criminal proceedings; the reasons and conditions that contributed to the commission of a criminal offense;2) circumstances related to the identity of the victim, including: socio-demographic characteristics of the victim, place of work, position held; official and functional responsibilities, the victim’s belonging to a law enforcement agency during the commission of a criminal offense against him; the type and scope of damage caused to the victim;3) circumstances related to the identity of the offender, namely: socio-demographic data of the offender, physiological and psychological condition, gender, citizenship, financial status, place of work, the record of criminal conviction and the facts of bringing to administrative liability; the presence of dependent disabled people; the presence of guilt in the form of direct intent, the purpose of the action; circumstances that aggravate or mitigate the punishment of the offender are grounds for releasing from criminal liability or punishment that exclude criminal liability; presence of accomplices.
Keywords: a criminal offense; circumstances to be clarified; law enforcement agency; interference into the activity.